Micronucleus Frequency in Exfoliated Buccal Cells of Children Living in an Industrialized Area of Apulia (Italy) - Panico, Alessandra (Int J Environ Res Public Health, 2020)
Micronuclei (MN) are biomarkers of early biological effect often used for detecting DNA damage in human population exposed to genotoxic agents. The aim of this study was to evaluate the frequency of MN in exfoliated buccal cells of children living in an industrialized (impacted) area compared with that found in children living in a control area without significant anthropogenic impacts. A total of 462 6–8-year-old children (206 in the impacted area, 256 in the control area) attending primary school were enrolled. A questionnaire was administered to the parents of the recruited children to obtain information about personal data, lifestyles, and food habits of their children. Atmospheric particulate fractions were collected near the involved schools to assess the level of environmental exposure of the children. The presence of MN was highlighted in 68.4% of children living in the impacted area with a mean MN frequency of 0.66‰ ± 0.61‰. MN positivity and frequency were significantly lower in the control area (37.1% and 0.27‰ ± 0.43‰, respectively). The frequency of MN was positively associated with quasi-ultrafine particulate matter (PM(0.5)), traffic near the home, and consuming barbecued food; while adherence to the Mediterranean diet and practicing sport were negatively associated.